2014
DOI: 10.1073/pnas.1406103111
|View full text |Cite
|
Sign up to set email alerts
|

Size-based molecular diagnostics using plasma DNA for noninvasive prenatal testing

Abstract: Noninvasive prenatal testing using fetal DNA in maternal plasma is an actively researched area. The current generation of tests using massively parallel sequencing is based on counting plasma DNA sequences originating from different genomic regions. In this study, we explored a different approach that is based on the use of DNA fragment size as a diagnostic parameter. This approach is dependent on the fact that circulating fetal DNA molecules are generally shorter than the corresponding maternal DNA molecules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
246
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(259 citation statements)
references
References 39 publications
8
246
2
2
Order By: Relevance
“…The same sequencing depth of 3.5 million reads was used like in our previous study on trisomy 21,18, and 13 and sex chromosome aneuploidies (12). To confirm that our technique provided results consistent with our previous study, we first assessed the ability of SSP to detect aneuploidy in our cohort.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The same sequencing depth of 3.5 million reads was used like in our previous study on trisomy 21,18, and 13 and sex chromosome aneuploidies (12). To confirm that our technique provided results consistent with our previous study, we first assessed the ability of SSP to detect aneuploidy in our cohort.…”
Section: Resultssupporting
confidence: 58%
“…To identify the full sequences of cfDNA, we used in-house Perl scripts to exclude incomplete reads and determine the size distributions of plasma cfDNA molecules. Fetal DNA is generally shorter than maternal DNA (28), resulting in the feasibility of predicting the fetal DNA concentration in maternal plasma (18). Plasma samples with a higher fetal DNA fraction would have a higher proportion of short plasma DNA fragments (∼130-140 bp; region A) and a lower proportion of long plasma DNA fragments (∼155-175 bp; region B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that ccffDNA can first be observed as early as 4 gestation weeks and the amount of ccffDNA increases as the pregnancy progresses [22] but diminishes quickly after the birth of the baby, so that it is no longer detectable in the maternal blood approximately 2 h after birth. The fetal DNA is significantly smaller than the maternal DNA in the bloodstream, with fragments with a median size of 146 bp and makes its way into the maternal bloodstream via shedding of the placental microparticles into the maternal bloodstream [23]. Fetal ccffDNA is heavily diluted with maternal plasma and this "fetal fraction" is positively correlated with gestational age while preliminary evidence suggests that it is negatively correlated with maternal weight [7,24,25].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…In general, the fetal fraction percentage has to be provided and to be estimated with real-time quantitative PCR [22,26]: over 8% is considered satisfactory for most NIPT methods, while a 4-8% is considered marginal [11]. There are now research efforts ongoing for the extraction of the fetal DNA from the maternal plasma based on its size in order to distinguish it from the maternal DNA and/or accurately estimate it [23].…”
Section: Cell-free Dnamentioning
confidence: 99%